Necessary Light - Fargnoli, Patricia (Utah State University, University Libraries, 1999)
May Swenson Poetry Award Volume 3, with foreward by Mary Oliver. ""I think the two attributes that will most impress readers are, first, the almost shimmering gladness with which Ms. Fargnoli replies to the gifts of beauty and of human love; and, second, the compassion with which she addresses whatever is beyond her own intimate surroundings. Whatever it costs her, whatever it takes, there seems to be for Ms. Fargnoli only one world and only one way to live within it: with a ferocity of attention, care, and response."" Mary Oliver